2019
DOI: 10.4324/9780429283666
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Land Uses in Africa

Abstract: The multifunctional land use cases presented in this book reaffirm the urgent need to invest in diverse farming systems as we work to develop sustainable, productive, climate smart agricultural systems. More importantly, the research highlights the importance of considering the varying circumstances of vulnerable communities when devising interventions and actions.' Sithembile Ndema Mwamakamba, Food, Agriculture and Natural Resources Policy Analysis Network (FANRPAN) 'This case-study approach to shifting patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 108 publications
(152 reference statements)
0
1
0
Order By: Relevance
“…For the three major global food crops, wheat, maize and rice, a recent review [4] indicated a yield gap of around 50%, and it is even larger in some parts of the world where the African continent has fallen behind the Green Revolution boom and shows large gaps. The current yields of maize, millet, and rice in Africa are only half of those in Asia [6].…”
Section: Introductionmentioning
confidence: 99%
“…For the three major global food crops, wheat, maize and rice, a recent review [4] indicated a yield gap of around 50%, and it is even larger in some parts of the world where the African continent has fallen behind the Green Revolution boom and shows large gaps. The current yields of maize, millet, and rice in Africa are only half of those in Asia [6].…”
Section: Introductionmentioning
confidence: 99%